2020
DOI: 10.1055/a-1160-9833
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine Treatment During the Perinatal Stage Prevents the Alterations in the ObRb-STAT3 Leptin Signaling Pathway Caused by Congenital Hypothyroidism

Abstract: Thyroid hormone deficiency during crucial stages of development causes congenital hypothyroidism. This syndrome alters hypothalamic pathways involved in long-term bodyweight regulation as ObRb-STAT3 leptin signaling pathway, which is associated with metabolic syndrome. This study aimed to determine if thyroxine treatment during pregnancy and lactation in hypothyroid mothers avoids, in the congenital hypothyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Also, in previous studies, we have reported the status of thyroid function at various stages of development using the same experimental model as the one used for the present work. The results obtained show that thyroid function in congenital hypothyroid pups remains low throughout development ( 12 , 13 , 14 ).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Also, in previous studies, we have reported the status of thyroid function at various stages of development using the same experimental model as the one used for the present work. The results obtained show that thyroid function in congenital hypothyroid pups remains low throughout development ( 12 , 13 , 14 ).…”
Section: Resultsmentioning
confidence: 83%
“…Rats fed a hypercaloric diet for 40 weeks had the highest hyperleptinemia levels with physiological leptin resistance. But usually, the leptin resistance can only be demonstrated by a molecular evaluation of hypothalamic SOCS3 overexpression because energy intake does not change ( 14 , 15 ). The results obtained show that a mild disturbance in the lipid contents of the diet produces metabolic damage, causing dyslipidemia, hyperleptinemia, and alterations in cardiovascular risk markers as Castelli index I and II.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, neonatal excess in T3 levels, as that observed in Dio3-/- mice and neo-T4 rats, also influences the programming of HPT axis and leptin-melanocortin system ( 47 , 78 , 79 ). Low neonatal levels of thyroid hormone can also determine hypothalamic leptin signaling in adult life ( 80 ). However, we observed no alterations in that regard.…”
Section: Discussionmentioning
confidence: 99%